Phonological Variations in the Use of Javanese Language in the Central and Western Suburbs of Surabaya - Khusnul Khotimah; Luthfiyah, Nanda Putri (Ikaprobsi, 2024)
In the use of phonological variations of the Javanese language located in the central and suburban areas of Surabaya, unconsciously there are dialect differences which cause a variety of phonological variations in the form of vowel and consonant phonemes. This study aims to determine the variety of phonological variations, determine the types of phonemes, and find out the results of the analysis of phonemes used in Javanese in the central and suburban areas of Surabaya. The research method used is descriptive qualitative. The data taken comes from communication between researchers and residents living in the Surabaya area. This study uses an instrument in the form of interviews. The method used by researchers in collecting data is the method of observing and noting (SLC). The method used by researchers in analyzing the data is the equivalent method with the determinant element sorting technique (PUP). The result of this study is that the phonological variations used in Javanese in the central and outskirt areas of Surabaya have vowel phonemes in the form of /u/, /i/, /o/, /a/, /e/, and /ə/ and consonant phonemes in the form of /d/, /g/, /s/, /b/, /n/, /m/, /p/, /l/, /r/, /t/, /w/, /y/, /k /, /c/, /h/, and J/. The conclusion of this research is that there is a geographical location and linguistic phenomena that are used by residents in formal education at school, so that they can influence the Javanese language spoken. Pada penggunaan variasi fonologis Bahasa Jawa yang terletak di wilayah pusat dan pinggiran Surabaya secara tidak sadar terdapat perbedaan dialek yang menyebabkan adanya ragam variasi fonologis berupa fonem vokal dan konsonan. Penelitian ini mempunyai tujuan untuk mengetahui ragam variasi fonologis, mengetahui jenis fonem, dan mengetahui hasil dari analisis fonem yang dimanfaatkan dalam Bahasa Jawa di wilayah pusat dan pinggiran Surabaya. Metode penelitian yang dimanfaatkan adalah deskriptif kualitatif. Data yang diambil bersumber dari komunikasi peneliti dan penduduk yang tinggal di wilayah Surabaya. Penelitian ini menggunakan instrumen berupa wawancara. Metode yang dimanfaatkan untuk mengumpulkan data adalah metode simak libat catat (SLC). Metode yang digunakan peneliti dalam menganalisis data adalah metode padan dengan teknik pilah unsur penentu (PUP). Hasil dari penelitian ini adalah variasi fonologis yang digunakan pada Bahasa Jawa di wilayah pusat dan pinggiran Surabaya terdapat fonem vokal berupa /u/, /i/, /o/, /a/, /e/, dan /ə/ dan fonem konsonan berupa /d/, /g/, /s/, /b/, /n/, /m/, /p/, /l/, /r/, /t/, /w/, /y/, /k/, /c/, /h/, dan /j/. Simpulan dari penelitian ini yaitu, adanya letak geografis dan fenomena kebahasaan yang terbiasa digunakan oleh penduduk pada pendidikan formal di sekolah, sehingga dapat mempengaruhi Bahasa Jawa yang diujarkan.